Simple and efficient synthesis of thysanone methyl ether - Bulbule, Vivek J.; Koranne, Priti S.; Deshpande, Vishnu H.; Borate, Hanumant B. (Tetrahedron, 2007)
The synthesis of thysanone methyl ether is achieved by employing semivioxanthin methyl ether, which in turn is prepared by the tandem Michael addition of an anion of orsellinate to a substituted dihydropyrone. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: human pathogen; Michael addition; orsellinate derivative; semivioxanthin